(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose - The present study was designed to examine whether mathematics computer games improved young childrenâ€™s learning of number sense under three different conditions: when used individually, with a peer, and with teacher facilitation. Methodology - This study utilized a mixed methodology, collecting both quantitative and qualitative data. A random sample of 62 children distributed across four classrooms in a public pre-kindergarten center participated in the study. The four classrooms served as teacherfacilitated, peer-facilitated, individual play, and control classrooms. Several sources of data were used, including informal observations and the â€œTest of Early Mathematics Ability-3 (TEMA-3)â€ developed by Ginsburg and Baroody in 2003. Findings - The results showed that mathematics computer games improved childrenâ€™s understanding of number sense, especially when supported by a teacherâ€™s skillful facilitation and scaffolding. Significance - The results of the study are significant as they inform teachers who integrate computer mathematics games in their curriculum and highlight the importance of scaffolding in supporting children during play. The findings further emphasize that offering children computerbased games to play without proper support and scaffolding does not necessarily lead to better and improved learning of number sense.